2011
DOI: 10.1016/j.ejpb.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Benznidazole microcrystal preparation by solvent change precipitation and in vivo evaluation in the treatment of Chagas disease

Abstract: Benznidazole (BNZ) is traditionally used to treat Chagas disease. Despite its common use, BNZ has a poor water solubility and a variable bioavailability. The purpose of this study was to prepare BNZ microcrystals by solvent change precipitation and to study the effects of BNZ micronisation on therapeutic efficiency using a murine model of Chagas disease. The solvent change precipitation procedure was optimised in order to obtain stable and homogeneous particles with a small particle size, high yield and fast d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…The LLOQ was established as 0.15 μg/mL, given the criteria of precision and accuracy (Table 2). This LLOQ was lower compared with other published methods, demonstrating that the proposed method was more sensitive for the quantification of plasma BNZ (Salomon, 2012;Maximiano et al, 2011;Morilla et al, 2002; Moreira da Silva et al, 2012; Leonardi et al, 2013;Marsón et al, 2013;Morilla et al, 2003). The recovery test also showed the acceptance criteria for precision and accuracy (Table 3), demonstrating that the method of processing the sample was suitable for the analysis of BNZ in plasma.…”
Section: Methods Validationmentioning
confidence: 57%
See 1 more Smart Citation
“…The LLOQ was established as 0.15 μg/mL, given the criteria of precision and accuracy (Table 2). This LLOQ was lower compared with other published methods, demonstrating that the proposed method was more sensitive for the quantification of plasma BNZ (Salomon, 2012;Maximiano et al, 2011;Morilla et al, 2002; Moreira da Silva et al, 2012; Leonardi et al, 2013;Marsón et al, 2013;Morilla et al, 2003). The recovery test also showed the acceptance criteria for precision and accuracy (Table 3), demonstrating that the method of processing the sample was suitable for the analysis of BNZ in plasma.…”
Section: Methods Validationmentioning
confidence: 57%
“…In the search for new formulations of BNZ, some authors have reported new pharmaceutical technologies to improve the pharmacokinetics, bioavailability and dissolution of BNZ (Salomon, 2012;Maximiano et al, 2011;Morilla et al, 2002). In some of these studies, bioanalytical methods were developed for the quantification of BNZ in plasma with application in vivo studies to evaluate the pharmacokinetics of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizers have been utilized widely to prevent crystal growth by providing steric hindrance due to the absorption at the drug-solvent interface during particle precipitation [34,35,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an in situ micronization technique without any mechanical process was developed recently by means of solvent precipitation with the addition of polymeric stabilizers in order to avoid the agglomerates 46. Maximiano et al47 described the preparation of benznidazole microcrystals by solvent change precipitation and its inclusion into tablets as an alternative solid dosage form, which is capable of overcoming that limitation and delivers the drug at optimal concentration for the desired therapeutic effect. The formation of crystals of reduced sized was carried out by means of a saturated solution of benznidazole prepared with selected organic solvents and water.…”
Section: Benznidazole Microcrystalsmentioning
confidence: 99%